PENGARUH PENCAK SILAT TERHADAP MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK ISLAM MESJID RAYA JIHAD KOTA PADANG PANJANG - Shabilla Putri, Chantika; Suryana, Dadan; Ismet, Syahrul; Yeni, Indra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the problem that some children have not developed gross motor skills. Motor development is the coordination of movements involving large muscles. The stimulation used for gross motor development is using pencak silat in the form of movement patterns. The purpose of this study is to quantitatively determine the effect of pencak silat movements on gross motor skills of early childhood. This study uses quantitative research with a quasi-experimental design. Data analysis uses a paired t-test with the aim of determining the effect of pencak silat movements on children's gross motor skills before and after being given treatment in the experimental group. The results of this study show an average value obtained by the experimental group of 20.71 which is higher than the control group with an average result of 17.50. The results of the increase are strengthened by using a paired t-test in the experimental group with a sig. (2-tailed) value of 0.000 <0.05. The results of data calculations can prove that there is an effect of pencak silat on gross motor skills of early childhood.